Usability of a Hybrid System Combining P300-Based Brain-Computer Interface and Commercial Assistive Technologies to Enhance Communication in People With Multiple Sclerosis - Riccio, Angela; Schettini, Francesca; Galiotta, Valentina; Giraldi, Enrico; Grasso, Maria Grazia; Cincotti, Febo; Mattia, Donatella (Frontiers in Human Neuroscience, 2022)
Brain-computer interface (BCI) can provide people with motor disabilities with an alternative channel to access Assistive Technology (AT) software for communication and environmental interaction. Multiple Sclerosis (MS) is a chronic disease of the central nervous system that mostly starts in young adulthood and often leads to a long-term disability, possibly exacerbated by the presence of fatigue. MS patients have been rarely considered as potential BCI end-users. In this pilot study, we evaluated the usability of a hybrid BCI (h-BCI) system which enables both a P300-based BCI and conventional input devices (ie., muscular dependent) to access mainstream applications through the widely used AT software for communication “Grid 3”. Evaluation was performed according to the principles of the User-Centered Design (UCD) with the aim at providing MS patients with an alternative control channel (ie. BCI), potentially less sensitive to fatigue. A total of 13 patients with MS were enrolled. In session I participants were presented with a widely validated P300-based BCI (P3-speller); in session II they had to operate Grid 3 to access three mainstream applications with a) an AT conventional input device (training) and b) the h-BCI. Eight patients completed the protocol. Five out of 8 MS patients were successfully able to access the Grid3 via the BCI, with a mean online accuracy of 83.3% (±14.6). Effectiveness (online accuracy), satisfaction, and workload were comparable between the conventional AT inputs and the BCI channel in controlling the Grid3. As expected, the efficiency (time for correct selection) resulted significantly lower for the BCI with respect to the AT conventional channels (Z=0.2, P<0.05). Although with caution due to the limited sample size, these preliminary findings indicated that the BCI control channel did not have a detrimental effect with respect to conventional AT channels on the ability to operate an AT software (Grid 3). Therefore, we inferred that the usability of the two access modalities was comparable. The integration of BCI with commercial AT input devices to access a widely used AT software represents an important step toward the introduction of BCIs into the AT centers’ daily practice.